Daytime activity budgets of feral goats (Capra hircus) on the Isle of Rum: Influence of season, age, and sex - Shi, J; Dunbar, R; Buckland, D; Miller, D (2003)
The activity budgets of feral goats (Capra hircus) on the Isle of Rum, northwest Scotland, were studied from January to December in 1981 and from May to November in 2000. We investigated differences in activity patterns in relation to season, time of day, and age-sex classes of goats, and their possible causes. Since the goats spent the night sleeping (or resting) in caves or other sheltered sites, only diurnal activity budgets were considered. Activity patterns were very similar between the two study periods (from May to November). All age-sex classes of feral goats spent most of the daytime feeding in both years, especially during autumn and winter. Feral goats increased the percentage of daytime that they spent feeding and decreased their resting time from summer to autumn-winter in response to the decrease in available day length and, possibly, the decrease in forage quality and biomass. Feral goats on Rum had two or three daily peaks of feeding in summer, but showed no obvious daily feeding peaks in winter, although their percentage of feeding time remained relatively high throughout the daytime in winter. No significant differences in general activity budgets between adult males and females were found, but yearlings were found to spend more time feeding than adults and kids. Adult males spent more time in social activities than did other age-sex classes, and adult males sharply decreased the percentage of daytime that they spent feeding during rutting periods, which may have contributed to their higher mortality over the subsequent autumn and winter.